Головные уборы крымских татар ХІХ - начала ХХ веков - Аблямитова, Л. (Матеріали до української етнології, 2007)
In the article, the author presents a classification of headdresses of Crimean Tatars. Exposes the original expressive language of the head-dresses of Crimean Tatars.